2021
DOI: 10.3389/fncel.2021.602888
|View full text |Cite
|
Sign up to set email alerts
|

NGN2 mmRNA-Based Transcriptional Programming in Microfluidic Guides hiPSCs Toward Neural Fate With Multiple Identities

Abstract: Recent advancements in cell engineering have succeeded in manipulating cell identity with the targeted overexpression of specific cell fate determining transcription factors in a process named transcriptional programming. Neurogenin2 (NGN2) is sufficient to instruct pluripotent stem cells (PSCs) to acquire a neuronal identity when delivered with an integrating system, which arises some safety concerns for clinical applications. A non-integrating system based on modified messenger RNA (mmRNA) delivery method, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…The second direction, also known as forward programming, is based on forcing the phenotypic change by acting on transcription factors to acquire a defined cellular epigenetic state. This approach is achieved by inducing expression of transcription factors that enable epigenetic remodeling into the target phenotype (39,40). These two extreme strategies do not need to be mutually exclusive, and the second one is accompanied by exogenous administration of growth factors and small molecules.…”
Section: Human Pluripotent Stem Cell Differentiation At the Microscalementioning
confidence: 99%
See 1 more Smart Citation
“…The second direction, also known as forward programming, is based on forcing the phenotypic change by acting on transcription factors to acquire a defined cellular epigenetic state. This approach is achieved by inducing expression of transcription factors that enable epigenetic remodeling into the target phenotype (39,40). These two extreme strategies do not need to be mutually exclusive, and the second one is accompanied by exogenous administration of growth factors and small molecules.…”
Section: Human Pluripotent Stem Cell Differentiation At the Microscalementioning
confidence: 99%
“…Tolomeo et al (39) developed a neuron differentiation protocol in microfluidics that forced the acquisition of a neuronal phenotype by inducing the expression of the neurogenin 2 (NGN2) transcription factor in hiPSCs. NGN2 expression was induced by multiple mRNA transfections, as exogenous mRNA persists in the cells for approximately 48 h. Unexpectedly, they found that inducing NGN2 expression by mRNA produced, besides neurons, 20-50% of neural stem cells, a subpopulation that was absent using other delivery methods.…”
Section: Forward Programmingmentioning
confidence: 99%
“…To make NGN2 iNs clinically relevant, many hurdles linked to the integration of foreign DNA must be overcome, such as varying expression levels and random integrations in coding or regulatory sequences. Recent efforts have been made to overcome those limitations by testing modified messenger RNA-based methods to produce NGN2 iNs ( Tolomeo et al., 2021 ). Overall, NGN2 iNs offer an exciting avenue in neuronal replacement therapy for both CNS injury or tumors; however, there are many hurdles including the ethical implications and the effects of newly converted neurons on function, memory, cognition, and behavior.…”
Section: Applications Of Ngn2 Insmentioning
confidence: 99%
“…In a study by Tolomeo et al. microfluidic platform was used in high efficiency delivery of Neurogenin-2 modified m-RNA (mmRNA) for neuronal transcriptional programming in hiPSCs [ 103 ]. Also, this microfluidic devices was previously used for high efficient transfection in mmRNA-based reprogramming [ [104] , [105] , [106] ].…”
Section: Single Neuron On-chip Drug Delivery and Analysismentioning
confidence: 99%